Chemical Immunology and Allergy 2005
DOI: 10.1159/000087965
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Reproductive Immunology for Other Fields of Immunology and Clinical Approaches

Abstract: Reproduction is indispensable to evolution and, thus, life. Nonetheless, it overcomes common rules known to established life. Immunology of reproduction, and especially the tolerance of two genetically distinct organisms and their fruitful symbiosis, is one of the most imposing paradox of life. Mechanisms, which are physiologically used for induction of said tolerance, are frequently abused by pathogens or tumors intending to escape the host's immune response. Understanding the regulation of immune responses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…During PE, reduced levels of IL-10 have been observed in circulation and in the placenta (143, 146, 147). Previous studies have demonstrated IL-10 to be a potent cytokine that regulates vasculature function and prevents vascular dysfunction (131, 146).…”
Section: The Effect Of Decreased Tregs and Il-10 In Preeclampsiamentioning
confidence: 99%
“…During PE, reduced levels of IL-10 have been observed in circulation and in the placenta (143, 146, 147). Previous studies have demonstrated IL-10 to be a potent cytokine that regulates vasculature function and prevents vascular dysfunction (131, 146).…”
Section: The Effect Of Decreased Tregs and Il-10 In Preeclampsiamentioning
confidence: 99%
“…A voluminous research literature now indicates that pregnancy introduces broad and marked modulation of both innate and adaptive immune function (20)(21)(22)(23)(24). Interest in those immune alterations stemmed from the recognition that they are key factors in understanding how the semiallogeneic embryo escapes from rejection.…”
Section: Immunomodulation Associated With Pregnancymentioning
confidence: 99%
“…25,29,80,81), but also the release of various immunomodulatory molecules that have a systemic effect. MICA/B, s-HLA-G, IL-6, IL-10, transforming growth factor-h, and progesterone-induced blocking factor are often found at increased level in the circulation of both cancer patients and pregnant women and are thought to assist the tumor and the fetus to escape attack by the immune system (20,27,80,82).…”
Section: Does the Effect Of Pregnancy On Immune Functionmentioning
confidence: 99%
“…Further investigations in transplant immunology under gender-specific view are currently under way. [15][16][17] Conclusions Female donor hearts lead to a higher early mortality in male recipients and male donor hearts lead to better short-term results in female recipients. In long-term, corrected for early mortality, female donor hearts are superior-specifically in female recipients.…”
Section: Discussionmentioning
confidence: 97%